The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/europace/eur316
|View full text |Cite
|
Sign up to set email alerts
|

Role of implantable cardioverter defibrillator therapy in patients with acquired long QT syndrome: A long-term follow-up

Abstract: Appropriate ICD shocks are a common finding in patients with aLQTS and SCA irrespective of the underlying cause or structural heart disease. Thus, even in the presence of relevant acquired proarrhythmia ICD may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…It should be highlighted, however, that an unknown percentage of supposedly high risk drug induced long QT patients have congenital LQTS and would therefore be entitled to an ICD implantation according to current recommendations. Moreover, the study by Mönnig et al supported the need for a more aggressive preventive strategy in ALQTS patients surviving cardiac arrest 26. This study suggested the proarrhythmic risk in this study population is not due solely to a transient trigger but an underlying persistent predisposition or exposure to other as yet unrecognised factors that cause QT prolongation.…”
Section: Clinical Managementsupporting
confidence: 57%
See 1 more Smart Citation
“…It should be highlighted, however, that an unknown percentage of supposedly high risk drug induced long QT patients have congenital LQTS and would therefore be entitled to an ICD implantation according to current recommendations. Moreover, the study by Mönnig et al supported the need for a more aggressive preventive strategy in ALQTS patients surviving cardiac arrest 26. This study suggested the proarrhythmic risk in this study population is not due solely to a transient trigger but an underlying persistent predisposition or exposure to other as yet unrecognised factors that cause QT prolongation.…”
Section: Clinical Managementsupporting
confidence: 57%
“…Their study was the first to use a continuous multi-lead QT/QTc monitoring system to examine QT prolongation in an acutely ill hospitalised population, and the authors suggested it could be prudent to provide QT monitoring to all acutely ill patients with multiple risk factors for QT prolongation. A study by Mönnig et al brought invaluable data to our current understanding of the real risk underlying ALQTS 26. The authors evaluated the long term follow-up of patients with ALQTS who had received an ICD for secondary prevention of sudden cardiac arrest and reported that appropriate shocks occurred in 44% of patients during a mean follow-up of 84±55 months—128 shocks in 19 of 43 patients, secondary to polymorphic VT and ventricular fibrillation.…”
Section: Clinical Managementmentioning
confidence: 99%
“…1, 2 Occasionally, the condition is congenital, caused by mutation(s) in one of the genes encoding cardiac ion channel subunits or auxiliary proteins. 37 More commonly, it is acquired, 810 caused by exposure to certain medications, electrolyte abnormalities or coronary ischemia. The mechanism linking action potential (AP) prolongation to ventricular arrhythmias remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Patients that progress to TdP should receive intravenous magnesium sulphate and trans-venous cardiac pacing [41,42]. In patients that develop VF the use of an ICD should also be considered [43].…”
Section: Discussionmentioning
confidence: 99%